Dynamic effects of short-term exercise on muscle texture and gut flora in the hybrid (Megalobrama amblycephala♀ × Ancherythroculter nigrocauda♂) - Wei, Huijie; Zhang, Lang; Li, Qing; Yu, Yali; Sun, Yanhong; Song, Ziwei; Li, Pei; Mao, Tao; Chen, Jian; He, Li; Wang, Guiying (Frontiers in Marine Science, 2022)
Fillet texture plays a significant role in consumer acceptance, which heavily influenced by exercise according to previous studies. “Xianfeng No. 2”, a novel hybrid of Megalobrama amblycephala (M. amblycephala) (♀) and Ancherythroculter nigrocauda (A. nigrocauda) (♂), with characteristics of quick growth, good disease resistance, and anti-stress capability, is one of an important aquaculture fish species in China, however, the ways to improve fillet quality in this species remains unknown. In this study, a short-term exercise trial (0-16d), hematoxylin and eosin (H&E) staining, and texture analysis were carried out to determine the effects of exercise on muscle cellularity and texture. Furthermore, 16S rRNA analysis was performed to determine the impacts of exercise on the intestinal microbiota. Compared with non-exercised group (0d), exercised groups showed influences in muscle cellularity (decreased muscle fiber diameter and increased muscle fiber density) and improvements in muscle texture (increased hardness, cohesiveness, gumminess, and chewiness). In addition, 16S rRNA sequencing analysis exhibited that short-term exercise could significantly increase the community richness and diversity, as well as alter the composition of gut microflora in this hybrid species. At the level of phylum, the relative richness of Proteobacteria, Firmicutes, Bacteroidetes, and Fusobacteria changed remarkably after short-term exercise. At the level of genus, the relative richness of Pseudomonas, Acinetobacter, Stenotrophomonas, Alpinimonas, Rhodococcus, Shewanella, Brevundimonas changed significantly, suggested that short-term swimming exercise might increase intrinsic antimicrobial resistance and promote denitrification capacity of this hybrid species. Furthermore, a LEfSe analysis of intestinal microflora communities illustrated that Pseudomonas and MNG7 may be utilized to distinguish between exercised and non-exercised fish. Our research, collectively, found an effective way to improve fillet texture by exercise, revealed the impacts of exercise on the intestinal microbiota, further expanded our knowledge of fish under exercise.